OPTIMIZING SOLAR IRRADIANCE ABSORPTION BY GRAPHENE-COATED SPHERICAL CORE-SHELL NANOPARTICLE - Fitriyadi
The optical responses of spherical silica–metal coated with graphene nanoparticles were simulated using quasi-static approximation. We applied the Drude-Lorentz model to calculate the permittivity of metals (gold, silver, and copper) and the Kubo model for graphene's permittivity. The simulation results show a new absorption peak in low frequency, which is the effect of the graphene layer. Graphene's thickness influences the permittivity of graphene and can shift the absorption peak moving to a long light wavelength. On the other hand, the solar irradiance absorption performances by the DMG nanoparticles depend on the core's radius, metal shell thickness, and the medium's refractive index. All DMG nanoparticles' optimum radii and thicknesses for solar irradiance absorption are 10 nm and 5 nm. The performances decrease when the shell's thickness becomes more significant for a fixed total size. Meanwhile, the medium's high refractive index increases the absorption performance, and the red-shift phenomenon happens. The DMG nanoparticle that has the best performance is the silver DMG nanoparticle.